Analisis Sistem Pembiayaan Pada PT Federal International Finance Cabang Jambi - Tumanggor, Cindia; Taufik , Haviz; Saputri , Eka Julianti Efris (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the financing system at PT Federal International Finance Jambi Branch in 2026, including the processes of application, creditworthiness analysis, disbursement, monitoring, collection, as well as the constraints, effectiveness, and problems encountered. This study employed a descriptive qualitative method, with data collected through in-depth interviews, observation, and documentation. The informants consisted of the Branch Manager, Credit Analyst, Marketing Officer, and Collection Officer. The results show that the financing system has been implemented in a structured manner in accordance with Standard Operating Procedures (SOP), covering all stages from application to collection. However, in practice, several constraints were identified, particularly external factors such as inaccurate customer data, unstable income, and uncooperative customer behavior. In addition, several problems were found, including discrepancies between SOP and field conditions, limitations of data in credit analysis, pressure to achieve financing targets, and challenges in the collection process. The effectiveness of the financing system is considered fairly good but not yet optimal, as problematic financing still occurs. Therefore, improvements are needed in customer data validation, inter-departmental coordination, and strengthening monitoring systems to be more adaptive to field conditions.